The impact of depression on survival of head and neck cancer patients: A population-based cohort study - Huang, Ren-Wen; Chang, Kai-Ping; Marchi, Filippo; Loh, Charles Yuen Yung; Lin, Yu-Jr; Chang, Chee-Jen; Kao, Huang-Kai (Frontiers in Oncology, 2022)
Background: Depression is common among patients with head and neck cancer, thereby affecting their survival rate. However, whether close monitoring of depression affects the survival outcomes of these patients is unknown. Therefore, this study aimed to determine whether depression treatment continuity after the diagnosis of cancer affects the survival of these patients. Methods: A total of 55,069 patients diagnosed with head and neck cancer in the Cancer Registration System database in Taiwan were enrolled. This cohort was followed from January 1, 2007 to December 31, 2017. Furthermore, the patients were divided into four groups, namely, “no depression,” “pre-cancer only,” “post-cancer only,” and “both before and after cancer,” on the basis of the diagnosis of depression and the duration of the follow-up period in the psychiatric clinic. Further, the Cox proportional hazard model was applied to estimate the hazard of death for the four groups. Results: A total of 6,345 (11.52%) patients were diagnosed with depression in this cohort. The “pre-cancer only” group had a lower overall survival (HR = 1.18; 95% CI = 1.11–1.25) compared with the “no depression” group. Moreover, the “post-cancer only” group had better overall survival (HR = 0.88; 95% CI = 0.83–0.94) compared with the “no depression” group, especially in advanced-stage patients. Patients who were diagnosed with depression before cancer and had continuous depression treatments after the cancer diagnosis had better overall survival (HR = 0.78; 95% CI = 0.71–0.86) compared with patients who had treatment interruptions. Conclusion: Patients with pre-cancer depression had poorer survival outcomes, especially those who did not receive psychiatric clinic visits after their cancer diagnosis. Nonetheless, in patients with advanced-stage cancer, depression treatment may improve overall survival.